Strategic Pathways to SMEs’ Competitiveness: The Roles of Financial Practices, Market Orientation, and Accounting Information Systems within Emerging Markets - Abubakar, Herminawaty; Faridah, Faridah; S, Nurhidayanti (STI Policy and Management Journal, 2025)
Small and Medium Enterprises (SMEs) play a vital role within emerging economies, such as Indonesia, yet many struggle to maintain competitiveness due to limited internal capabilities and uneven digital adoption. While market orientation and financial practices have been widely studied, few studies have examined how these strategic elements interact, particularly in the context of emerging markets where digital infrastructure and managerial resources are often constrained. This study addresses this gap by investigating the direct and indirect effects of Market Orientation and Strategic Financial Practices on Competitive Advantage, using Indonesia’s retail SMEs as the empirical setting. Grounded in Resource-Based View and Dynamic Capabilities Theory, the model incorporates three mediators: Innovation, Resource Allocation, and Financial Reporting Quality, and examines the moderating role of Accounting Information Systems (AIS). Data were collected from 500 SMEs managers and analyzed using Structural Equation Modeling (SEM). The results confirm the significant impact of both market and financial capabilities on Competitive Advantage, and demonstrate how these relationships are amplified by innovation, effective resource use, and financial transparency. AIS also positively moderates the financial strategy–performance link, highlighting its role in digital transformation. This study provides a holistic framework for enhancing SMEs’ competitiveness and offers practical insights for policymakers and SMEs development programs.